The supply of ecosystem services along an urban-rural gradient, in Johannesburg, South Africa - Jaxa, Busisiwe (University of the Witwatersrand, Johannesburg, 2024)
Currently, the entire world is experiencing an unparalleled process of urbanisation, which is marked by an increase in population, economic progress, and the spread of urban areas. Although urbanisation presents opportunities such as economic advancement, enhanced infrastructure, and improved living conditions, it also brings about adverse effects on the natural environment. Ecosystem services vary along urban-rural gradients as they are largely affected by land use and land cover change. There is an increasing focus on urban ecosystem services that enhance urban resilience. Nonetheless, there has been minimal research conducted in South Africa regarding the effects of urbanisation on the provision of ecosystem services. This study aimed to investigate the impact of urbanisation on ecosystem services in the greater Johannesburg area and provide a deeper understanding of how the provision of three specific ecosystem services has evolved. These ecosystem services included temperature regulation, flood regulation and carbon sequestration. The land surface temperature (LST) along each gradient was derived from the Landsat (5 TM, 7 ETM+, 8 OLI) datasets available in the Google Earth Engine. Carbon storage was determined by estimating biomass using basic tree measurements. Soil compaction was measured as a proxy for the flood regulation ecosystem service. Lasty, land cover change was also assessed with the use of the ArcGIS software. The findings revealed that the supply of ecosystem services increased with an increasing distance from the city centre. Temperature and soil compaction were found to be high at the urban end of the gradient and carbon storage was found to be low at the urban end of the gradient. The land cover assessment revealed that the City of Johannesburg has suffered a substantial loss of green spaces over the 20 years, as the area covered by built-up surfaces increased. This study, therefore, has how how green spaces in urban areas enhance the sustainability of cities by supporting the supply of various ecosystem services including flood and climate regulation, carbon sequestration and storage. It has also shown that, the rapid urbanisation that the city experienced has led to a reduction in the overall supply of ecosystem services, whilst rural landscapes on the other hand continue to maintain the provision of these services. In order to enhance the green infrastructure in urban areas, it is recommended that, the urban natural systems are integrated in the urban planning and infrastructure initiative
A Dissertation Submitted in fulfillment of the requirements for the degree Masters by Dissertation in Animal, Plant, and Environmental Sciences in the Faculty of Science, University of the Witwatersrand, Johannesburg, South Africa, 2024
Keywords: Ecosystem services; Urban green spaces; Urban-rural gradient; Temperature regulation; Flood regulation; Carbon sequestration; Land cover change; SDG-15: Life on land